2011
DOI: 10.1089/thy.2010.0191
|View full text |Cite|
|
Sign up to set email alerts
|

Hashimoto's Thyroiditis Affects Symptom Load and Quality of Life Unrelated to Hypothyroidism: A Prospective Case–Control Study in Women Undergoing Thyroidectomy for Benign Goiter

Abstract: Women with HT suffer from a high symptom load. Hypothyroidism is only a contributing factor to the development of associated conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
103
1
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 161 publications
(117 citation statements)
references
References 26 publications
8
103
1
5
Order By: Relevance
“…This finding means that hypothyroidism or hyperthyroidism, only were a contributing factor to the development and the presence of associated symptoms of disease. Our data are in concordance with study of Ott et al (10). They found that increased anti-TPO levels were associated with a lower quality of life and various general symptoms as chronic fatigue, dry hair, chronic irritability, chronic nervousness in Hashimoto's thyroiditis patients.…”
Section: Table 1 Stratification Of the Dimensions Of Eq-5dsupporting
confidence: 93%
“…This finding means that hypothyroidism or hyperthyroidism, only were a contributing factor to the development and the presence of associated symptoms of disease. Our data are in concordance with study of Ott et al (10). They found that increased anti-TPO levels were associated with a lower quality of life and various general symptoms as chronic fatigue, dry hair, chronic irritability, chronic nervousness in Hashimoto's thyroiditis patients.…”
Section: Table 1 Stratification Of the Dimensions Of Eq-5dsupporting
confidence: 93%
“…A previous study that specifically analyzed the correlation between chronic asthenia and thyroidectomy found patients who had undergone TT frequently complained of tiredness or asthenia in performing physical tasks and mental work [12]. It is well known that hypothyroidism, hyperthyroidism, and Hashimoto's thyroiditis may be associated with chronic asthenia [39,42]. However, thyroid surgery itself does not improve QoL except for specific symptoms such as compression.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, the impairment of thyroid dysfunction or thyroid eye disease on QoL is well established [2][3][4][5][6][7]. However, the negative influence of other thyroid disorders such as benign goitre or chronic autoimmune thyroiditis on patients' QoL has been suggested in recent studies [8][9][10][11].…”
Section: Quality Of Life In Patients With Benign Thyroid Disordersmentioning
confidence: 99%